PENILAIAN PRODUK DAN GRATIS BIAYA KIRIM PADA KEPUTUSAN PEMBELIAN DI SHOPEE - Kurniadi, Hanif (Buletin Studi Ekonomi, 2023)
The objective of this research is to examine how product evaluation and free shipping impact the buying decisions made on Shopee. This study's population consists of all Shopee users who live in Jambi City. This study involved a sample of 100 people. The sampling technique is nonprobability sampling - purposive sampling. The method used to collect data was through an online questionnaire, and the researchers employed several statistical methods such as multiple regression analysis, t-test, f-test, and the coefficient of determination. The study's outcomes suggest that purchasing decisions are influenced by product ratings at Shopee. Purchase decisions are influenced by free shipping at Shopee, and purchasing decisions are jointly influenced by product evaluation and free shipping at Shopee.